Relationship of Laser-Doppler-Flow and coronary perfusion and a concise update on the importance of coronary microcirculation in donor heart machine perfusion - Saemann, Lars; Großkopf, Anne; Hoorn, Fabio; Veres, Gábor; Guo, Yuxing; Korkmaz-İçöz, Sevil; Karck, Matthias; Simm, Andreas; Wenzel, Folker; Szabó, Gábor (Clinical hemorheology and microcirculation, 2021)
BACKGROUND: Machine perfusion (MP) is a novel method for donor heart preservation. The coronary microvascular function is important for the transplantation outcome. However, current research on MP in heart transplantation focuses mainly on contractil
Gesehen am 22.11.2021